Answer:
<h2>3x^2+2x−4=0</h2>
Use the quadratic formula to find the solutions
−b±√b^2−4(ac)/2a
Substitute the values
a=3, b=2, and c=−4 into the quadratic formula and solve for x.
−2±√2^2−4⋅(3⋅−4)/2⋅3
Simplify.
x = −1±√13/3
The final answer is the combination of both solutions.
x= −1−√13/3,−1+√13/3
The result can be shown in multiple forms.
Exact Form:
x= −1−√13/3,−1+√13/3
<h3>Decimal Form:</h3>
x=0.86851709…,−1.53518375…
Step-by-step explanation:
Hope it is helpful......
Answer:
It is 14. I split the shapes.
Step-by-step explanation:
Answer:
Step-by-step explanation:
It's two unequal real solutions.
a = 1
b = 7
c = 6
discriminate = sqrt(7^2 - 4*1*6)
discriminate = sqrt(49 - 24)
discriminate = sqrt(25)
discriminate = 5
Now you cannot determine what this means unless you put it in the quadratic formula
x = (-7 +/- 5)/2
x = (- 7 + 5) / 2
x = - 2/2 = - 1
x = (-7 - 5)/2
x = -12/2
x = - 6
You see that you have two unequal reals.
The answer is B. The product of two irrational numbers
Answer:
D. x=4 only
Step-by-step explanation:
x^2 – 8x + 16 = 0
(x - 4)^2 = 0
x - 4 = 0
x = 4